The Prophetic Methodology of Leadership through Education - Dr. Muhammad Zaid Malik (Seerat Studies, 2023)
Education is not just passing on information. It’s a complete process of formation. Prophet Muhammad, peace be upon him, prepared leaders out of Bedouins through education. How did he evolve an illiterate nation into the leaders of the world? What techniques did the Prophet SAW use to educate his companions to become future leaders? In what ways can the Prophetic methodology of leadership education be implemented today? This article will try to shed some light on these aspects of the comprehensive life of Prophet Muhammad, peace be upon him. In this paper inductive and analytical methods are used.